Correction: Increased Von Willebrand factor, decreased ADAMTS13 and thrombocytopenia in melioidosis - Birnie, Emma; Koh, Gavin C. K. W.; Löwenberg, Ester C.; Meijers, Joost C. M.; Maude, Rapeephan R.; Day, Nicholas P. J.; Peacock, Sharon J.; van der Poll, Tom; Wiersinga, W. Joost (PLoS neglected tropical diseases, 2020)
[This corrects the article DOI: 10.1371/journal.pntd.0005468.].[This corrects the article DOI: 10.1371/journal.pntd.0005468.].